Transmissão de vídeos com HTML5 - Valente, Gustavo Volpon (2013)
This monograph presents a proposal to playing educational videos on the internet, with the video element, defined in HTML5, the main concept discussed by exploring beyond the application of the element, information related to the video distribution architecture and APIs media. The project is aimed at the reduction of noise in communication that arise during the process of transmission of content in multimedia format in order to ensure continuous user experience.